Case Report: Hemoptysis localization - hearing with your eyes - Barry Chan (CINQUILL Medical Publishers Inc., 2016)
Clinical Vignette: 45 year old was transferred from a peripheral facility for acute massive hemoptysis though maintained sufficient airway patency with no evidence of hemodynamic instability or respiratory failure. Thoracic auscultation revealed vesicular breathing with no adventitious sound. CXR from the peripheral site was normal.